Cases with mild cognitive impairment and Alzheimer's disease fail to benefit from repeated exposure to episodic memory tests as compared with controls. - Schrijnemaekers, A; de Jager, C; Hogervorst, E; Budge, M (2006)
Memory tests may be predictive for cognitive decline. We investigated the sensitivity and change in performance over time of the Hopkins Verbal Learning Test (HVLT) and the Mini-Mental Status Examination (MMSE) for Mild Cognitive Impairment (MCI) and Alzheimer's Disease (AD) when compared to cognitively healthy controls. Participants included elderly controls (n = 54), MCI (n = 19) and AD cases (n = 28) from OPTIMA. The MMSE and the HVLT (version 1) were administered twice to all subjects with an interval of 2-3 years.MCI and AD cases had poorer performance than controls on the HVLT and MMSE at both testing episodes (p < 0.05). The HVLT profile over time showed a learning effect in the control group (P < 0.0001), a trend to decline in the AD group (p = 0.09) and no change in the MCI group (P = 0.8). A subgroup of MCI subjects had lower HVLT scores at follow-up. The MMSE profile showed no significant change over time for all three groups (P > 0.05). The HVLT had better sensitivity and specificity compared to the MMSE for detecting MCI and AD. The HVLT is not only valuable for cross-sectional designs but has also proved to be valuable in a longitudinal design. Cognitively healthy controls showed evidence of learning strategies on the HVLT after a 2-3 year interval, with improved scores at the second testing episode. By contrast, an MCI group showed no benefits of previous exposure to this test. Lack of use of learning strategies on the HVLT may be an important marker of the likelihood of cognitive decline to MCI or dementia.